Drug reprofiling history and potential therapies against Parkinson’s disease - Latif, Komal; Ullah, Aman; Shkodina, Anastasiia D.; Boiko, Dmytro I.; Rafique, Zakia; Alghamdi, Badrah S.; Alfaleh, Mohamed A.; Ashraf, Ghulam Md. (Frontiers in Pharmacology, 2022)
Given the high whittling down rates, high costs, and moderate pace of new medication, revelation, and improvement, repurposing 'old' drugs to treat typical and uncommon illnesses is progressively becoming an appealing proposition. Drug repurposing is the way toward utilizing existing medications in signs other than the ones they were initially designed for. Faced with scientific and economic challenges, the prospect of discovering new medication indications is enticing to the pharmaceutical sector. Medication repurposing can be used at various stages of drug development, although it has the most promise when the drug has previously been tested for safety. We describe strategies of drug repurposing for Parkinson's disease, which is a neurodegenerative condition that primarily affects dopaminergic neurons in the substantia nigra. Discuss the obstacles faced by the repurposing community and suggest new approaches to solve these challenges so that medicine repurposing can reach its full potential.